Evaluation of self-absorption of manganese emission lines in laser induced breakdown spectroscopy measurements - Bredice, Fausto Osvaldo (2006)
This paper is part o f a more general study aimed to the determination o f the best experimental procedures for reliable quantitative measurements o f F e-M n alloys by LIBS. In this work, attention is pointed on the self-absorption processes, whose effect deeply influences the LIBS measurements, reflecting in non-linear calibration curves. The effect o f self-absorption on the line intensity can be quantified by defining a self absorption coefficient, that measures the deviation o f the line intensity from the linear extrapolation o f the curve o f growth in the optically thin regime. The authors demonstrated in a previous paper that self absorption coefficients could be calculated once the electron density o f the plasma is known and the Stark coefficients o f the lines are available. However, when the Stark coefficients o f the lines o f interest are not known, a different approach is needed. In this work a new method for evaluation o f self absorption coefficients in LIBS measurements is presented, which does not require the knowledge o f Stark coefficients. In order to understand the basic principles and setting out the theoretical tools that w ill be used for the analysis o f the alloys, a preliminary study was done on pure Mn; LIBS spectra were acquired in different experimental conditions, at different laser energies and different delays after the laser irradiation o f the sample. Moreover, collinear double pulse measurements were also performed. Analytical relations were derived and experimental procedures devised for evaluation o f the self absorption coefficients o f several Mn lines, which are important for characterization and control o f the experimental conditions in which the analysis is performed.